2002
DOI: 10.1088/0264-9381/19/21/308
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational deflection of massive particles in classical and semiclassical general relativity

Abstract: We calculate the gravitational deflection of massive particles moving with relativistic velocity in the solar system to second post-Newtonian order. For a particle passing close to the Sun with impact parameter b, the deflection in classical general relativity is ΦC = 2GM/v20b[1 + v20/c2 + 3π/2 MG/bc2 + 3π/8 MG/bc2 v20/c2 + 9(MG/bc2)2], where v0 is the particle speed at infinity and M is the Sun's mass. We compute afterwards the gravitational deflection of a spinless neutral particle of mass m in the same st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
36
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 12 publications
9
36
0
1
Order By: Relevance
“…Interestingly, Accioly and Ragusa [34] have shown that in semi-classical general relativity, the bending of light is dependent on v c , and that when 0 v = , one gets the Soldner formula for Newtonian bending of light. When v c = one gets the Einsteinian bending of light result.…”
Section: Gravitational Light Deflectionmentioning
confidence: 99%
“…Interestingly, Accioly and Ragusa [34] have shown that in semi-classical general relativity, the bending of light is dependent on v c , and that when 0 v = , one gets the Soldner formula for Newtonian bending of light. When v c = one gets the Einsteinian bending of light result.…”
Section: Gravitational Light Deflectionmentioning
confidence: 99%
“…Gravitational deflection of massive particles has been studied by numerous authors, both in the general relativistic weak lensing limit (Lowenthal 1973), strong lensing limit (Tsupko 2014)and in semi-classical gravity (Accioly & Ragusa 2002;Accioly & Paszko 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The former equation gives the gravitational deflection angle for a massless particle, a result foreseen by Einstein a long time ago, whereas the latter just gives the prediction of general relativity for the bending of a massive particle by an external weak gravitational field [39]. The results of …”
Section: (E)mentioning
confidence: 98%